2018
DOI: 10.3390/met8020103
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Creep-Fatigue Behavior of Alloy 617

Abstract: This paper presents the high-temperature creep-fatigue testing of a Ni-based superalloy of Alloy 617 base metal and weldments at 900 • C. Creep-fatigue tests were conducted with fully reversed axial strain control at a total strain range of 0.6%, 1.2%, and 1.5%, and peak tensile hold time of 60, 180, and 300 s. The effects of different constituents on the combined creep-fatigue endurance such as hold time, strain range, and stress relaxation behavior are discussed. Under all creep-fatigue tests, weldments' cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The composition (wt.%) of the commercial-grade Alloys used in this study is shown in Table 1. The as-received microstructure of the alloy 617 is shown in Figure 1, showcasing a fully austenitic face-centered cubic (FCC) structure known for maintaining superior mechanical properties at high temperatures (Dewa et al, 2018a). Figure 2 shows the monotonic stress-strain behavior of Alloy 617, with FCC matrix, mainly consisting of nickel, cobalt, iron, chromium, and molybdenum.…”
Section: Methods and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The composition (wt.%) of the commercial-grade Alloys used in this study is shown in Table 1. The as-received microstructure of the alloy 617 is shown in Figure 1, showcasing a fully austenitic face-centered cubic (FCC) structure known for maintaining superior mechanical properties at high temperatures (Dewa et al, 2018a). Figure 2 shows the monotonic stress-strain behavior of Alloy 617, with FCC matrix, mainly consisting of nickel, cobalt, iron, chromium, and molybdenum.…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…Additionally, it provides good properties for components of power generating plants, gas turbines, and high temperature superior required applications. Alloy is now being widely used for high-temperature applications (Dewa et al, 2018a;Dewa et al, 2018b;Dewa et al, 2016;Ekaputra et al, 2016;Redy et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Where, P describes the combined effect of temperature and time and is a stress-dependent quantity, T is the operating temperature and t is the limit creep time 12 .…”
Section: Build a Life Prediction Modelmentioning
confidence: 99%
“…Several parametric models have been proposed for predicting the long-term failure time based on short-term measurement data [19][20][21]. The LMP model and the Monkman-Grant model are widely used for the estimation of the creep-buckling failure time [12,[22][23][24]. These models are both based on experimental measurements, but the Monkman-Grant model needs the minimum strain rate of the specimen.…”
Section: Empirical Correlation: Lmpmentioning
confidence: 99%